Representations of the female gender in selected local teen magazines a content analysis - Ramos, Maria Carmina B.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
The glossy magazine industry in the Philippines is a fast-faced, growing business. Leading local teen magazine titles such as Candy, MEG and Seventeen Philippines, in particular, reach a large young Filipina audience. This same audience is also part of the patron communities of academic libraries in local schools. It is with this in mind that this content analysis was undertaken.
Additionally, this study is doubly important because of RA9246, which stipulates that licensed librarians may now include not only library and information professionals, but also qualified elementary and high school teachers as well. The content analysis will be able to help not only in selection, acquisition, or anticipating young Filipinas' library needs, but also help in bridging generation and communication gaps by providing a common ground that is easy to understand for both librarian/teacher and patron/student. Out of the 33 magazines that comprised the 2006 issues of Candy, MEAAAAG and Seventeen Philippines, 15 were selected randomly to go through the coding process. Each issue yielded an average of 75 units of content, resulting in more than 1000 coded units.
The methodology was based on the foreign studies of Signorelli (1997) and Schlenker (1998), who both undertook content analysis of teen magazines. The data gathered from the content analysis revealed that the general physical representation of the young Filipina in local teen magazines is a combination of the following average build; straight, long, black hair; a mestiza complexion; wearing noticeable makeup; wearing sleeveless tops and long pants; being fully and casually clothed in a feminine looking outfit; having a neutral social acceptability (neither conservative nor daring); and actively maintaining a neutral stance (neither strong nor weak). This is a smart compromise of conservative Filipino values and current times. The general social representation of the young Filipina in local teen magazines shows that the young Filipina is interested in fashion, feature, beauty, and culture articles; articles in the category of self-development and appearance; and social motivations for reading articles, such as to have or keep a romantic relationship, or to be pro-social. Physical motivations ranked lower but were dominated by the desire to have better fashion sense. The majority of the magazine articles employed an aggressive method of imparting messages to young Filipinas. This shows a preoccupation with appearance, but also a desire for social development.
Recommendations included (a) using this content analysis as a springboard for further, similar studies; (b) focusing on audience research that will complement the methodology and results of this study; (c) doing a comparative analysis using the same methodology but different samples; and (d) taking the theoretical framework of this study and proceeding to conceptualize an original thesis with either a feminist or gender identity/representation slant. A final recommendation for librarians and educators is to still consider subscribing to local teen magazines, and to go a step further by educating young Filipinas in such a way that they become aware of the shortcomings of local teen magazines, and learn to read them without being negatively influenced while still getting the information that they do need.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Teenage girls in pop culture -- Philippines; Women in mass media; Teenagers in mass media; Youth's periodicals -- Philippines